2021
DOI: 10.1088/1674-1056/ac0bae
|View full text |Cite
|
Sign up to set email alerts
|

Quantum metrology with coherent superposition of two different coded channels*

Abstract: We investigate the advantage of coherent superposition of two different coded channels in quantum metrology. In a continuous variable system, we show that the Heisenberg limit 1/N can be beaten by the coherent superposition without the help of indefinite causal order. And in parameter estimation, we demonstrate that the strategy with the coherent superposition can perform better than the strategy with quantum switch which can generate indefinite causal order. We analytically obtain the general form of estimati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…It implements the controlled superposition of orders in which two (or more) unitaries (or, more generally, quantum channels) are applied to a target system. Among other aspects, it has been shown that with the help of QS one can gain computational advantages [2,[6][7][8], communication advantages [9][10][11] or even the super Heisenberg limit in metrology [12][13][14][15][16]. For example, it has been predicted [10] that completely depolarizing quantum channels (which have zero capacity, i.e., they do not transmit any information), if superposed with the help of the QS, can be used for information transmition.…”
Section: Introductionmentioning
confidence: 99%
“…It implements the controlled superposition of orders in which two (or more) unitaries (or, more generally, quantum channels) are applied to a target system. Among other aspects, it has been shown that with the help of QS one can gain computational advantages [2,[6][7][8], communication advantages [9][10][11] or even the super Heisenberg limit in metrology [12][13][14][15][16]. For example, it has been predicted [10] that completely depolarizing quantum channels (which have zero capacity, i.e., they do not transmit any information), if superposed with the help of the QS, can be used for information transmition.…”
Section: Introductionmentioning
confidence: 99%